204k views
3 votes
How do I solve 6/2 + 8/3

User Reddish
by
6.4k points

1 Answer

5 votes

Answer:

The solved given fractional expression is
(17)/(3)

Therefore the given fractional expression becomes


(6)/(2)+(8)/(3)=(17)/(3)

Explanation:

Given fractional expression is
(6)/(2)+(8)/(3)

To solve the given fractional expression as below :


(6)/(2)+(8)/(3)


=3+(8)/(3)


=(3* 3+8)/(3)

( here taking the term 3 as LCM )


=(9+8)/(3) ( by adding the sums here )


=(17)/(3)


(6)/(2)+(8)/(3)=(17)/(3)

Therefore the solved given fractional expression is
(17)/(3)

Therefore the given fractional expression becomes


(6)/(2)+(8)/(3)=(17)/(3)

The solved given fractional expression is
(6)/(2)+(8)/(3)=(17)/(3)

User Reed Sandberg
by
5.9k points